Implementation of the ISMUBA Curriculum in Shaping Islamic Character in Students at SD Muhammadiyah 1 Surakarta - Putri, Devy Ramandhani Dion; Muhroji, M (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to describe how the ISMUBA curriculum is implemented at SD Muhammadiyah 1 Surakarta, to outline the specific indicators of Islamic character embedded within that implementation, and to identify both the challenges encountered and the evaluation processes used in carrying out the curriculum. Methodology: Employing a descriptive qualitative approach, the research was conducted at SD Muhammadiyah 1 Surakarta with the curriculum itself as the object of study. Participants included the curriculum vice principal, teachers, and students in grades 2 and 5. Data were gathered through interviews with school leaders and educators, classroom and congregational observations, and review of relevant documentation. To ensure validity, the study used source triangulation—drawing on multiple informants—and technique triangulation— using various data‐collection methods. Data analysis proceeded through the stages of reduction, presentation, and conclusion drawing. Results: Implementation began with detailed planning, followed by regular ISMUBA activities such as murojaah, Quran memorization, Quran writing exercises, and congregational dhuha, dhuhr, ashar, and Friday prayers. The curriculum integrates three key indicators of Islamic character: faith and piety, noble morals, and social responsibility. Internally, the program faces challenges related to differing teacher competencies and student abilities; externally, it must adapt to shifting national education policies, notably the flexibility required by the Kurikulum Merdeka. Applications/Originality/Value: By mapping the full cycle from planning to evaluation, this study provides a replicable model for other primary schools aiming to incorporate faith‑based character development into their curricula. It highlights the importance of systematic evaluation and ongoing teacher training as effective strategies for mitigating competency gaps and policy changes, offering practical insights for educators and administrators seeking to enhance Islamic character education.